درجة توافر مهارات إدارة الأزمات لمديري مدارس التعليم الثانوي في محافظة دمشق من وجهة نظر المدرسين - صاصيلا رانيا; اليوسفي رنيم سمير (Latakia University Journal - Arts and Humanities Sciences Series, 2014)
تهدف الدراسة إلى تعرف درجة توافر مهارات إدارة الأزمات لمديري مدارس التعليم الثانوي في محافظة دمشق من وجهة نظر المدرسين وتعرف دلالة الفروق بين متوسطات تقديرات المدرسين في محافظة دمشق لدرجة توافر مهارات إدارة الأزمات لدى مديري مدارس التعليم الثانوي طبقاً للمتغيرات التالية: (الجنس- وعدد سنوات الخدمة - والمؤهل العلمي والتربوي)ـ ولتحقيق أهداف الدراسة تم بناء استبانة، مؤلفة من (53) بنداً، موزعة إلى خمسة مجالات. طُبقت على عينة مؤلفة من (302) مدرساً ومدرسة، خلال الفصل الأول من العام الدراسي2012/2013م. أظهرت النتائج أن المتوسط الحسابي لدرجة توافر مهارات إدارة الأزمات لمديري مدارس التعليم الثانوي في محافظة دمشق ككل حصل على تقدير متوسط وفقاً لإجابات أفراد عينة البحث، وتبين عدم وجود فروق دالة إحصائياً حول درجة توافر إدارة الأزمات لدى مديري مدارس التعليم الثانوي وفق متغيري (الجنس، وسنوات الخدمة)وذلك عند كل مجال وعلى مستوى المجالات كافة، بينما ظهرت فروق دالة إحصائياً في تقدير مدرسي المرحلة الثانوية لدرجة توافر إدارة الأزمات لدى مديريهم في محافظة دمشق وفق متغير المؤهل العلمي والتربوي لصالح أفراد عينة البحث من ذوي حملة الشّهادة الأعلى. The aim of this research is to know the availability of crisis management skills on the part of directors of secondary schools in the province of Damascus from the viewpoint of teachers, focusing on the significance of the differences between the averages of the estimates in the governorate of Damascus regarding the availability of crisis management skills by managers to the following variables: (gender-number of years of service-qualification and education). To achieve the aims of this research a questionnaire of 53 items has been devised and distributed to five fields. It was applied to a sample of (302) teachers in Damascus schools in the first term the academic year 2012/2013. Results showed that median availability of skill crisis management by directors as a whole got average estimate according to the answers given. There were no statistical differences about the availability of crisis management by the directors of secondary schools according to the variables of gender, years of service at each level, in all of the areas, while there were statistically some differences in estimating high school teachers of the availability of management crisis managers in the governorate of Damascus under variable qualification and education for members of the sample jobs with higher degree holders.